Royal jelly extracellular vesicles promote wound healing by modulating underlying cellular responses - Simón Álvarez; Pamina Contreras-Kallens; Sebastian Aguayo; Orlando Ramírez; Catalina Vallejos; Jorge Ruiz; Eva Carrasco-Gallardo; Stefanie Troncoso-Vera; Bernardo Morales; Christina M.A.P. Schuh (Elsevier, 2023)
Apis mellifera royal jelly (RJ) is a well-known remedy in traditional medicine around the world and its versatile effects range from antibacterial to anti-inflammatory properties and pro-regenerative properties. As a glandular product, RJ has been shown to contain a substantial number of extracellular vesicles (EVs), and, in this study, we aimed to investigate the extent of involvement of RJEVs in wound healing-associated effects. Molecular analysis of RJEVs verified the presence of exosomal markers such as CD63 and syntenin, and cargo molecules MRJP1, defensin-1, and jellein-3. Furthermore, RJEVs were demonstrated to modulate mesenchymal stem cell (MSC) differentiation and secretome, as well as decrease LPS-induced inflammation in macrophages by blocking the mitogen-activated protein kinase (MAPK) pathway. In vivo studies confirmed antibacterial effects of RJEVs and demonstrated an acceleration of wound healing in a splinted mouse model. This study suggests that RJEVs play a crucial role in the known effects of RJ by modulating the inflammatory phase and cellular response in wound healing. Transfer of RJ into the clinics has been impeded by the high complexity of the raw material. Isolating EVs from the raw RJ decreases the complexity while allowing standardization and quality control, bringing a natural nano-therapy one step closer to the clinics.